Observasi Dampak Pelebaran Jalan Terhadap Kondisi Alam Di Sekitar Bukit Tirtifui di Desa pailelang, Kecamatan Alor Barat Daya, Kabupaten Alor - bani, kezia; Melki Imamastri Puling Tang; Nehemia Fanpada; Yulia Jemau; Meri Sarah Padamani; Paulina Da Silva (Jurnal Kajian dan Penelitian Umum, 2023)
Abstract Mid the growth in the number of vehicles will increase the movement and use of transportation infrastructure. Road widening is one of the actions that can be used as a solution, but along with a road widening solution, traffic performance will also increase. Widening the road on the hill will also have both good and bad effects. To determine the impact of road widening on natural conditions around the Tirtifui hill, it is necessary to carry out research and analysis. Research conducted using qualitative research, with data collection techniques namely interviews, observation and documentation. From the results of the analysis, it was found that road widening is one of the factors that can affect the natural conditions around the Tirtifui hill. From this study we conclude that the occurrence of indiscriminate felling of trees causes landslides during the rainy season and makes it difficult for people to work during the rainy season, during the dry season there is prolonged heat. The destruction of rocks that are prone to landslides are rocks that are on the slopes with rock types, namely small sediments and rocks that come from mountains, usually the rocks on the slopes are weathered or have no strength and easily crumble into soil, this triggers landslides, high rainfall is one of the causes of landslides during the long dry season the soil will dry and form soil pores (soil cavities) and then cracks occur in the soil when rain comes automatically rain water goes into the soil cavities or the open soil pores earlier water rain that fills the cavity causes a shift in the soil which eventually results in landslides and soil eruptions